Digital traceability in horticulture: a systematic review of edge-cloud-blockchain-terminal (ECBT) integration with IoT and AI technologies - Huang, Yan; Li, Xin; Xu, Luyi; Ma, Yongqiang (Frontiers in Blockchain, 2025)
Global horticultural supply chains face escalating vulnerabilities from pathogenic outbreaks, climate disruptions, and regulatory demands. This systematic mini-review examines the Edge-Cloud-Blockchain-Terminal (ECBT) framework—an integrated architecture positioning blockchain as the trust backbone connecting distributed computing, edge intelligence, and user terminals—for comprehensive traceability. Following PRISMA guidelines, we analyzed 40 high-quality studies selected from 156 peer-reviewed articles retrieved from Web of Science, Scopus, and IEEE Xplore databases (2022–2025) using combined technology (“IoT” OR “blockchain” OR “AI” OR “edge computing”) and application (“traceability” OR “supply chain”) search terms. Technology coverage analysis revealed fragmented adoption: IoT dominates (45%, n = 18), followed by blockchain (32%, n = 13) and AI/ML (23%, n = 9), with only 3% achieving full ECBT integration despite demonstrated benefits. Blockchain implementations achieve 94.2% storage optimization through selective anchoring while maintaining cryptographic verification, with latency reduced by 73% through the CRPBFT consensus mechanism. While edge computing achieves a 65% reduction in latency, its integration with blockchain’s global state management presents persistent architectural challenges. Critical barriers persist: technical interoperability (23% metadata loss in cross-chain transitions), economic exclusion (42% of smallholder annual income for deployment), and scalability constraints (processing 47 million daily data points). The review identifies blockchain’s triple role as trust orchestrator, semantic preservator, and incentive aligner as key to overcoming the integration paradox. Future research should focus on agricultural-specific consensus, semantic interoperability, and inclusive deployment models to resolve the integration paradox.